Surficial fractures in the Navajo sandstone, south‐western USA: the roles of thermal cycles, rainstorms, granular disintegration, and iterative cracking. Issue 9 (11th May 2020) - Loope, David B.; Loope, Garrison R.; Burberry, Caroline M.; Rowe, Clinton M.; Bryant, Gerald C.
Abstract: Deep (> 5 m) sheeting fractures in the Navajo sandstone are evident at numerous sites in southern Utah and derive from tectonic stresses. Strong diurnal thermal cycles are, however, the likely triggers for shallow (< 0.3 m) sheeting fractures. Data from subsurface thermal sensors reveal that large temperature differences between sensors at 2 and 15 cm depth on clear summer afternoons are as great as those that trigger sheeting fractures in exposed California granite. Extensive polygonal patterns in the Navajo sandstone are composed of surface‐perpendicular fractures and were produced by contractile stresses. Numerous studies have shown that porewater diminishes the tensile strength of sandstone. Based on our thermal records, we propose that cooling during monsoonal rainstorms triggers polygonal fracturing of temporarily weakened rock. On steep outcrops, polygonal patterns are rectilinear and orthogonal, with T‐vertices. Lower‐angle slopes host hexagonal patterns (defined by the dominance of Y‐vertices). Intermediate patterns with rectangles and hexagons of similar scale are common. We posit that outcropping fractures are advancing downward by iterative steps, and that hexagons on sandstone surfaces (like prismatic columns of basalt) have evolved from ancestral orthogonal polygons of similar scale. In lava flows, fractures elongate intermittently as they follow a steep thermal gradient (the source of stress) as it rapidly moves through the rock mass. In our model, a steep, surficial thermal gradient descends through unfractured sandstone, but at the slow pace of granular disintegration. Through time, as the friable rock on stable slopes erodes, iterative cracking advances into new space. Hexagonal patterns form as new fractures, imperfectly guided by the older ones, propagate in new directions, and vertices drift into a configuration that minimizes the ratio of fracture length to polygon area. © 2020 John Wiley & Sons, Ltd. Abstract : Surface exposures of the Navajo Sandstone display beautiful fracture patterns. The fractures can be rectilinear or hexagonal or a mix of the two patterns. The first fractures to form are rectilinear with "T" junctions where fractures join or cross. If the land surface is relatively steep, this pattern is retained until it is destroyed by rock falls or rock slides. If the land surface slopes more gently, the pattern can change to a hexagonal one (with "Y" junctions) as the rock surface is slowly lowered by erosion.